Tes Keterampilan Dribbling Pemain Futsal SMK Muhammadiyah - Dwiyanto, Jefri (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2025)
This research aims to find out and then describe and compare the dribbling technical skills of futsal players at SMK Muhammadiyah 4 Kalisat with the application of soccer dribbling instruments and the application of futsal dribbling test instruments in carrying out dribbling technical skills. The method used in the research is a type of comparative descriptive research with a quantitative approach. This research is a survey research method; tests and measurements must be carried out to obtain real data. Data collection uses a futsal dribbling skills test from research. The t-test results from this research show that the futsal test instrument variable has better results, namely 3.833 > 2.179, t is in the Ho rejection area. The second exercise provides a better improvement in dribbling ability in futsal sports games. This means that the more often you practice, the better the ball dribbling ability of futsal players will be. Conclusion: There is a difference between the training results using futsal test instruments and soccer instruments. Keywords: Dribbling, Skill